1992
DOI: 10.1104/pp.99.4.1635
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transport and Phosphorylation of Tonoplast Polypeptides from Zucchini Are Stimulated by the Phospholipid Platelet-Activating Factor

Abstract: The ether phospholipid platelet-activating factor and certain similar phospholipids, including lysophosphatidylcholine, are known to stimulate both H' transport and protein phosphorylation in plant microsomal membranes. In the present work, several polypeptides in highly purified tonoplast membranes from zucchini (Cucurbita pepo L.) showed platelet-activating factor-dependent phosphorylation. Comparison of protein phosphorylation in different membrane fractions separated by sucrose step density gradient centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…We believe that these are due to modifications of Vma2p which alter its charge-to-mass ratio. It has been shown that Vma2p is phosphorylated in both plant and animal systems (47,48), and there is recent evidence that it is also phosphorylated in yeast. 2 At least one modification may be dependent upon Vma4p, since an unusual band appears in gel-resolved extracts from the ⌬vma4 strain, with Vma2p as the only detectable component.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that these are due to modifications of Vma2p which alter its charge-to-mass ratio. It has been shown that Vma2p is phosphorylated in both plant and animal systems (47,48), and there is recent evidence that it is also phosphorylated in yeast. 2 At least one modification may be dependent upon Vma4p, since an unusual band appears in gel-resolved extracts from the ⌬vma4 strain, with Vma2p as the only detectable component.…”
Section: Discussionmentioning
confidence: 99%
“…NTAP-SOS2 purification identified five subunits (A, B1/2/3, C, E1, and G1) of the V-ATPase peripheral (cytoplasmic) sector as being components of a SOS2-containing protein complex. Of these subunits, VHA-A is responsible for the binding and hydrolysis of ATP, VHA-B is involved in noncatalytic ATP binding and, it has also been suggested, has a regulatory role, and VHA-C, VHA-E, and VHA-G are involved in the assembly and coupling of the peripheral and integral membrane sectors of the V-ATPase complex (29,34,44,51,54).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous yeast two-hybrid screen using SOS2 as the bait protein identified not only ABI2 (33) but also VHA-B and several other clones as putative interactors with SOS2 (data not shown). VHA-B, together with VHA-A, controls the binding of ATP, whose hydrolysis is then catalyzed by VHA-A alone while VHA-B, it has been suggested, has a role in regulating the activity of the V-ATPase complex (29,44,54). To confirm the interaction between VHA-B proteins and SOS2, the entire open reading frames of VHA-B1 and VHA-B2 were fused with the GAL4 activation domain in the prey plasmid pACT2 and cotransformed with the bait plasmid pAS-SOS2, pAS-SOS2 K40N, or pAS-SOS1 (33) into the yeast strain Y190.…”
Section: Analysis Of Tap-tagged Sos2 Identifies V-atpase Subunits As mentioning
confidence: 99%
“…Little is known about the mechanisms that regulate V-ATPase and V-PPase activities in plants. It has been postulated that phosphorylation of the B subunit of the V1 domain of the V-ATPase plays a role in regulating the activity of the enzyme (Martiny-Baron et al, 1992). Other mechanisms proposed to regulate the V-ATPase are cytosolic pH (Davies et al, 1994) and the redox state of the cytosol (Feng and Forgac, 1992;Muller et al, 1996).…”
Section: Discussionmentioning
confidence: 99%